2004
DOI: 10.2460/javma.2004.225.384
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the prevalence of heart murmurs in overtly healthy cats

Abstract: Results indicated that heart murmurs are detectable in a large proportion of overtly healthy cats and that many murmurs appear to be caused by structural heart disease that is in a clinically latent state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 15 publications
(14 reference statements)
3
32
1
Order By: Relevance
“…17 The progression of HCM is variable with many cats having a long asymptomatic period that may end with the abrupt development of congestive heart failure, arterial thromboembolism, or sudden cardiac death. Potential negative prognostic indicators for decompensation of HCM include increased left atrial size 8,9 and elevated heart rate (HR).…”
Section: Introductionmentioning
confidence: 99%
“…17 The progression of HCM is variable with many cats having a long asymptomatic period that may end with the abrupt development of congestive heart failure, arterial thromboembolism, or sudden cardiac death. Potential negative prognostic indicators for decompensation of HCM include increased left atrial size 8,9 and elevated heart rate (HR).…”
Section: Introductionmentioning
confidence: 99%
“…Two multibreed studies done on dogs with DCM demonstrated survival after 1 year of being diagnosed with DCM at only 17.5% and 37.5%, respectively, with the median survival times of only 27 and 65 days, respectively. 11 This is in comparison to studies conducted in the 1970s and 1980s where only 1.6% of all cats referred to a veterinary hospital were reported to have HCM. However, in the late 1980s Pion et al 9 reported an association with DCM and taurine deficiency in cats.…”
Section: Type and Incidencementioning
confidence: 78%
“…Thus, although HCM had become the most common feline cardiac disease by the late 1980s and the 1990s, it was still not considered to affect a large percentage of the feline population. However, a recent publication reported that 21% of overtly healthy cats had a cardiac murmur [3]. Eighty-six percent of these cats that subsequently underwent echocardiography had structural cardiac disease, primarily HCM [3].…”
Section: Hcmmentioning
confidence: 96%
“…However, a recent publication reported that 21% of overtly healthy cats had a cardiac murmur [3]. Eighty-six percent of these cats that subsequently underwent echocardiography had structural cardiac disease, primarily HCM [3].…”
Section: Hcmmentioning
confidence: 96%
See 1 more Smart Citation